Geographical and seasonal variation in water hemlock (Cicuta maculata) toxins. (April 2020) - Stonecipher, Clinton A.; Welch, Kevin D.; Lee, Stephen T.; Cook, Daniel; Pfister, James A.
Abstract: Water hemlock ( Cicuta spp.) plants are typically found in wet areas and are toxic to all species of livestock. The toxic components in water hemlock are C17 polyacetylenes, with cicutoxin being the most studied. The objective of this study was to evaluate the variation in cicutoxin and total C17 polyacetylene compounds in water hemlock populations across western North America. Cicutoxin and total C17 polyacetylene concentrations varied among the six collection locations and among plant parts. Tubers contained the highest cicutoxin and total C17 polyacetylene concentrations of all plant parts. Green seeds contained the second most abundant total C17 polyacetylene concentrations. Total C17 polyacetylene and cicutoxin concentrations were also compared in different plant parts at several different phenological stages over the growing season. Cicutoxin and total C17 polyacetylene concentrations in the tubers increased until the green seed stage whereupon the concentrations decreased as the seeds matured and the plant began to senesce. Concentrations of secondary compounds in the stems were consistent with the optimal defense theory in which secondary compounds were higher in stems in earlier development stages compared to later stages and concentrations in seeds were higher than other above ground parts. The toxic compounds are found in all plant parts, with tubers posing the most significant risk of livestock poisoning. Results presented in this study suggest that the toxic risk to livestock likely does not differ between water hemlock ( Cicuta maculata ) populations across western North America under similar circumstances of ingestion. Highlights: Total C17 polyacetylene and cicutoxin concentrations vary among plant parts of water hemlock ( Cicuta maculata ). Tubers contain the highest cicutoxin and total C17 polyacetylene concentrations. Tubers from water hemlock pose the most significant risk of livestock poisoning. Water hemlock populations across western North American likely pose a similar poisoning risk to livestock.